2022
DOI: 10.3390/toxins14020128
|View full text |Cite
|
Sign up to set email alerts
|

Different Algicidal Modes of the Two Bacteria Aeromonas bestiarum HYD0802-MK36 and Pseudomonas syringae KACC10292T against Harmful Cyanobacteria Microcystis aeruginosa

Abstract: Blooms of harmful cyanobacteria Microcystis aeruginosa lead to an adverse effect on freshwater ecosystems, and thus extensive studies on the control of this cyanobacteria’s blooms have been conducted. Throughout this study, we have found that the two bacteria Aeromonas bestiarum HYD0802-MK36 and Pseudomonas syringae KACC10292T are capable of killing M. aeruginosa. Interestingly, these two bacteria showed different algicidal modes. Based on an algicidal range test using 15 algal species (target and non-target s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Out of the two bacterial strains, Pseudomonas fluorescens BG‐E exhibited the highest percentage of cell lysis against two species of Pseudanabaena . As discussed in previous studies, the bacterial species belonging to the genus Pseudomonas was capable of lysing cyanobacteria (Kang et al, 2012; Park et al, 2022; Ren et al, 2010; Zhang et al, 2011) and diatoms (Kang et al, 2005) in both marine and freshwater environments. For instance, the bacterial species, P. fluorescens SK09 isolated from the Paldang reservoir in Korea exhibited the potential to lyse harmful freshwater diatom Stephanodiscus hantzschii (Jung et al, 2008).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Out of the two bacterial strains, Pseudomonas fluorescens BG‐E exhibited the highest percentage of cell lysis against two species of Pseudanabaena . As discussed in previous studies, the bacterial species belonging to the genus Pseudomonas was capable of lysing cyanobacteria (Kang et al, 2012; Park et al, 2022; Ren et al, 2010; Zhang et al, 2011) and diatoms (Kang et al, 2005) in both marine and freshwater environments. For instance, the bacterial species, P. fluorescens SK09 isolated from the Paldang reservoir in Korea exhibited the potential to lyse harmful freshwater diatom Stephanodiscus hantzschii (Jung et al, 2008).…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, the present study also observed a high percentage of cell lysis (>50%) in P. lonchoides LW1 only when its cell density was less than 0.15 (OD 730 nm). The recent findings of Park et al (2022) showed that the bacterium Pseudomonas syringae KACC10292 completely lysed cells of M. aeruginosa regardless of its initial cell density whereas Aeromonas bestiarum HYD0802-MK36 caused 100% cell lysis only when the cell density of M. aeruginosa was 5 × 10 4 cells • mL −1 . Thus, the reported difference in the percentages of cell lysis with the changing inoculum densities of P. lonchoides LW1 and Pseudanabaena sp.…”
Section: Discussionmentioning
confidence: 98%
“…Against pathogenic M. aeruginosa, recently discovered algicidal bacteria A. bestiarum HYD0802-MK36 and P. syringae KACC10292T have been found to be effective [103]. The growth of M. aeruginosa can be hampered by a number of bacteria from the genera Aeromonas [104] and Pseudomonas [105].…”
Section: Microorganisms Controlmentioning
confidence: 99%
“…Proteobacteria, which is divided into five parts, is one of the most widespread and extensively studied bacteria in the microbiology field, and it is well known to effectively biodegrade cyanobacteria and diatoms in eutrophic environments [2,10]. The majority have been identified as members of Pseudomonas [18,19], Aeromonas [20,21], Acinetobacter [22], Raoultella [23], Brevundimonas [24], Ochrobactrum [25], Halobacillus [26], Shewanella [27], Citrobacter [28], Stenotrophomonas [29], Serratia [30] and Hahella [31] genera belonging to the γ-Proteobacteria class.…”
Section: Anticyanobacteriamentioning
confidence: 99%
“…In addition to B. cereus, other anticyanobacteria that destroy M. aeruginosa with direct attack have also been reported. For example, the anticyanobacterial modes of Aeromonas bestiarum HYD0802-MK36 [20], Chryseobacterium sp. [40], Streptomyces globisporus G9 [83], Alcaligenes denitrificans [59], and Shigella sp.…”
Section: Anticyanobacterial Modesmentioning
confidence: 99%